Kemiskinan, Uang, dan Gaya Hidup Sosialisme Karya Sastra Keep The Aspidistra Flying Karya George Orwell - Natasya Choirin Nur Fildzah; Sukma Dwi Melida; Eva Dwi Kurniawan (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
Poverty can be a big problem for the country. By not having property, human life becomes completely limited. The lack of shelter, food and clothing facilities means they cannot meet their living needs as they should. Poverty is the main problem in the novel Keep The Aspidistra Flying where the main character suffers from poverty since birth. In the story, even though Gordon Comstock, the main character in this novel, was born into a poor family, he really hates money and state capitalism. He prefers to live independently with simplicity and persistence. This novel research uses the Hermeneutics method. Hermeneutics is a method that regulates methods of interpretation, namely the interpretation of texts and other signs that can be considered texts. This problem of poverty must be resolved immediately, otherwise many bad impacts will arise, one of which is long-term poverty.